SIMILES IN GEORGE BAMBER’S RETURN TO DUST - Putri, Eka Ananda; Br.Pardede, Tama Riska; Bahri, Syamsul (CALL, 2022)
The objective of this study was to investigate similes in George Bamber's Return to Dust. This study used descriptive qualitative in order to explore the kinds of simile in the dialogue utterance of characters in such drama. The results found that the most frequent kind was descriptive simile 40%, close simile 35%, illustrative simile 15%, open simile 5% and illuminative simile 5%. Descriptive simile occurs on a character named James and Daphne as a scientist while describing the things in their work of experiments. A closed simile occurs in James's utterance when comparing the definition of one object to the tenor. Illustrative similes were also found in James's utterance while describing the process of experiment in science. Open and illuminative similes were found while explaining the quality of the condition and comparing the character to scientific experiments. Similes were used in the drama Return to Dust in describing something in order to create a lasting impression in the readers’ minds. Keywords: simile, drama, return to dust